Web3. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2023)
"Blockchain and crypto aren't just for speculators anymore-they're the basis of the rising decentralized internet. Web3 has the potential to rewrite the past decade's rules: Monopolies may be shattered, fortunes will be made and lost, and new classes of products and services will emerge. Where does your business fit in? Web3: The Insights You Need from Harvard Business Review will show you how today's most innovative organizations are choosing Web3, evaluating their risks, experimenting with their brands, and preparing to win in the newer, better internet age"--
Web3 Will Run on Cryptocurrency: A Q&A with crypto expert Jeff John Roberts / by Ramsey Khabbaz -- Why Blockchain's Ethical Stakes are So High: How developers and users can mitigate potential harm in Web / by Reid Blackman -- What a DAO Can -- and Can't -- Do: An introduction to decentralized autonomous organizations / by Jonathan Ruane and Andrew McAfee -- Why Build in Web: It has the potential to unlock a more valuable internet-for everyone / by Jad Esber and Scott Duke Kominers -- How Brands are Experimenting with Web: What early adopters are getting right / by Ana Andjelic -- Cautionary Tales from Cryptoland: A Q&A with software engineer and Web3 critic Molly White / by Thomas Stackpole -- Web3 Is Our Chance to Make a Better Internet: A theory of justice for a new era / by Li Jin and Katie Parrott.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: World Wide Web -- Technological innovations; Business -- Data processing; Blockchains (Databases) -- Industrial applications; Cryptocurrencies; Web applications; Business -- Data processing; Cryptocurrencies; Web applications